Evaluation of Wood Vinegar as an Herbicide for Weed Control - Lei Chu; Haifeng Liu; Zhenyu Zhang; Yue Zhan; Kang Wang; Deyu Yang; Ziqiang Liu; Jialin Yu (Agronomy, 2022)
Wood vinegar, a by-product of wood pyrolysis, is mostly discarded. Wood vinegar has a phytotoxic effect and could be potentially used as a naturally derived herbicide for weed control. The objective of this research was to evaluate the efficacy of wood vinegar from the pyrolysis of apple (Malus × domestica Borkh.) tree branch wastes to control weeds. The wood vinegar concentrations required to inhibit 50% motherwort (Leonurus cardiaca L.), redroot pigweed (Amaranthus retroflexus L.), Spanish needles (Bidens pilosa L.), and tall fescue (Festuca arundinacea L.) seed germination measured 0.51%, 0.48%, 0.16%, and 1.1%, respectively. The wood vinegar application rates (spray volume) required to provide 50% control of motherwort and Spanish needles measured 1911 L ha−1 and 653 L ha−1, respectively, while the highest evaluated rate at 4000 L ha−1 controlled 35% tall fescue by 10 days after treatment (DAT). Common purslane (Portulaca oleracea L.) control increased as the wood vinegar application rate increased from 500 L ha−1 to 2000 L ha−1. Wood vinegar was more effective in dark than light conditions for controlling common purslane. By 5 DAT, averaged over application rates, wood vinegar provided 95% and 87% control of common purslane in dark and light conditions, respectively. These findings suggest that wood vinegar obtained from the pyrolysis of apple tree branches could be used for weed management.